New service development: strategy and process in the hospitality sector in Kenya - (:unkn) unknown (My University, 2015)
This paper addresses the issue of new service development (NSD) process in the hospitality sector. While it is recognized that there are significant differences between service sectors, much less has been written about differences between separate services, with most studies concentrating on financial services. The aim of the study is to investigate to what to what extent findings in the financial services sector are applicable to the hospitality service sector and whether NSD is significantly different for “high contact” services as opposed to “low-contact” services. Utilizing a survey of industry managers in Kenya data will be collected in the areas of NSD strategy and process. This paper tries to fill this gap by integrating the empirical findings from both quantitative and qualitative data. The study will employ a cross-sectional, survey based methodology and qualitative case studies. The Kenyan sampling frame will include classified hotels.
Thesis research proposal
This paper addresses the issue of new service development (NSD) process in the hospitality sector. While it is recognized that there are significant differences between service sectors, much less has been written about differences between separate services, with most studies concentrating on financial services. The aim of the study is to investigate to what to what extent findings in the financial services sector are applicable to the hospitality service sector and whether NSD is significantly different for “high contact” services as opposed to “low-contact” services. Utilizing a survey of industry managers in Kenya data will be collected in the areas of NSD strategy and process. This paper tries to fill this gap by integrating the empirical findings from both quantitative and qualitative data. The study will employ a cross-sectional, surveybased methodology and qualitative case studies. The Kenyan sampling frame will include classified hotels.
Keywords: New service development; hospitality; services marketing; strategy; process